Dietary polyunsaturated fatty acids and cancers of the breast and colorectum: emerging evidence for their role as risk modifiers - Bartsch, Helmut; Nair, Jagadeesan; Owen, Robert (Carcinogenesis, 1999)
Abstract. The hypothesis that a high-fat diet promotes the development of postmenopausal breast cancer is supported by international data showing a strong corre
Gesehen am 02.02.2021